The Influence of Service Quality and Facilities on Patient Satisfaction at the General Outpatient Clinic (Journal of Social And Education Research, 2025)
Patient satisfaction is the main indicator of the success of a health service provider. If the patient is satisfied with the quality of service and facility provided by the healthcare service, it will have a positive impact on the institution. Patient satisfaction can also increase the interest of patient to revisit. This research aimed to determine the influence of service quality and facilities on patient satisfaction at Cakranegara Community Health Center. The method employed in this research was quantitative method with 91 respondents. The hypotheses were tested using the multiple linier regression analysis with SPSS 20 version. The result of the simple linier regression analysis showed that the significant values for the service quality and facilities were 0.002 and 0.000 respectively. These values were smaller than 0.05 which indicated that the test result was significant. Moreover, the MANOVA test result was 0.000 which was smaller than 0.05, this means that service quality and facilities of the health service significantly influence patient satisfaction. In conclusion, the good quality of service supported by adequate facilities offered by Cakranegara Community Health Center can provide comfort and pleasant experience for patients which in return increased patient satisfaction.